Improving Patient Comprehension of Numeric Health Information. (September 2015) - Azevedo, Renato F. L.; Morrow, Daniel; Hasegawa-Johnson, Mark; Gu, Kuangxiao; Soberal, Dan; Huang, Thomas; Schuh, William; Garcia-Retamero, Rocio
Our goal is to improve understanding and use of numeric information (e.g., clinical test results) provided through portals to Electronic Health Record (EHR) systems by older adults with diverse numeracy and risk literacy abilities. We help older adults understand this information by emulating in portal environments best practices from face-to-face communication. To do this, we are developing a computer-based agent (CA) that will use nonverbal cues (e.g. voice intonation, facial expressions) as well as words to convey affective and cognitive meaning of the numbers and improve patient comprehension of the clinical information. The present paper describes a pilot study designed to evaluate the appropriateness and effectiveness of audio-video messages of a physician delivering clinical test results. These messages will serve as a template for the development of the CA. Older adult pilot participants generally understood the gist of the test results presented in the video messages. Participants' affective responses to the messages were appropriate to the message's level of risk: as the level of risk associated with the test results increased, positive affect decreased and negative affect increased. In addition, participants also thought the physician's delivery matched the message content, and they thought that the messages were informative. These findings will be leveraged to finalize the materials for the primary study in which the impact of video and CA-based messages on patient comprehension of numeric information will be evaluated relative to standard formats used in patient portals.